Pengaruh Electronic Word of Mouth (E-WoM) terhadap Keputusan Pembelian Tiket Film Oppenheimer - Fahlevy, Erlangga Putra; Pribadi, Muhammad Adi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Creating films is a risky business that requires a profound understanding of audience motivation and strategies to bring them to the cinemas. In the digital era, electronic word of mouth (e-WoM) as a means to exchanging information on social media, particularly through platforms like X, plays a key role in influencing film ticket purchase decisions. e-WoM activities on X, such as tweets and retweets, serve as crucial indicators of a film's popularity. However, it is essential to note that popularity on social media is not always positive. This motivates the aim of this research, which focuses on examining the influence of e-WoM on X on the decision to purchase tickets of film